Stimulation of the subthalamic nucleus improves velocity of ballistic movements in Parkinson's disease. - Joundi, R; Brittain, J; Punt, T; Green, A; Jenkinson, N; Aziz, T (2012)
High-frequency stimulation of the subthalamic nucleus can markedly improve motor function in patients with Parkinson's disease. However, the underlying mechanisms mediating these improvements are not well understood. In particular, whether motor function is differentially improved in distal or proximal movements is not fully determined. Also, whether reaction time is improved along with other motor parameters is still a matter of debate. Here, we test patients OFF and ON subthalamic nucleus stimulation by capturing simple ballistic movements across four joints using kinematic motion analysis. We show that velocity, but not reaction time, is significantly improved with stimulation. There was no strong differential effect between joints. These results add evidence that deep brain stimulation of the subthalamic nucleus can enhance performance of ballistic movements in Parkinson's disease, and demonstrate that the subthalamic nucleus may be important in driving parameters of motor control after the response has been initiated.